Nature and level of work participation of the members of NAGKAKAISA in Lapaz, Iloilo City - Mamburan, Mary Ederline Tesoro (1995.)
The study described the nature of work participation of members of NAGKAKAISA, analyzed the level of their work participation with respect to selected variables and described the effect of the woman's participation in the labor market on the gender division of labor and decision-making in the home. Primary data were gathered by interviewing 60 members of NAGKAKAISA using purposive sampling. The study used two by two tables in analyzing the level of work participation with respect to selected characteristics. The characteristics included where: gae, number of years married, number of children, income, education, work experience, normative conflict, time conflict, and husband-wife dominance in decision-making. Level of work participation was categorized into high, low and no participation. The study found out that the level of work participation of respondents are mostly low. The nature of their work participation are mostly in petty trading, labor and income-earning home production. The jobs usually entered by respondents are marginal and in the formal sector. The characteristics selected did not explain the difference in the level of work participation of women except for normative conflict which showed a certain pattern with respect to level of work participation. The researcher recommended the following to improve the level of work [participation of members of NAGKAKAISA: reorient men's attitude towards greater sharing in the home as well women's significant contribution to production; provision of access to services such as child care, health services, and credit; upgrading skills including in those jobs traditionally dominated by men; provisiopn of income generating activity that do not add to their domestic burden; employment opportunities must be accompanied with raising the level of conciousness of women reagrding their market role and lastly, employment opportunities must be balanced for men and women to encourage favorable attitude toeards working women.
Thesis (Undergraduate, Bachelor of Arts in Economics) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Working Women